Hydrogen Desorption Properties of MgH2 + 10 wt% SiO2 + 5 wt% Ni Prepared by Planetary Ball Milling - Malahayati Malahayati; Evi Yufita; Ismail Ismail; Mursal Mursal; Rinaldi Idroes; Zulkarnain Jalil (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
MgH2 is a very hopeful material for application as hydrogen storage material in the solid form. This is due to its reversibility and its ability to store large amounts of hydrogen, which is 7.6 wt%. However, this material still has weaknesses, namely high operating temperature and slow kinetic reactions. Various attempts have been made to overcome this weakness, including downsizing and adding catalyst. In this study, double catalyst was used, namely natural silica extracted from rice husk ash and nickel nano powder, with a composition of MgH2 + 10 wt% SiO2 + 5 wt% Ni. The purpose of this research was to study the effect of downsizing and using these catalysts to the thermodynamic and kinetic properties of the hydrogen storage material MgH2. Samples were prepared by using High Energy Ball Milling (HEBM), with variations in milling time of 1, 5, 10, and 15 hours. The X-ray Diffraction (XRD) pattern showed the presence of an impurity phase in the samples milled for 10 and 15 hours. It also showed a reduction in grain size with increasing milling time. However, agglomeration has occurred in the samples milled for 15 hours. From the Scanning Electron Microscope (SEM) results can be seen that the sample with longer milling time, were homogeneously distribute. Thermal investigation showed that the lowest desorption temperature was achieved in samples with milling time of 5 and 10 hours, namely 287 °C and 288 °C. This study shows that natural silica catalyst plays a role in improving the thermodynamic characteristics of MgH2, while Ni plays a role in improving the kinetic characteristics of MgH2. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).